2020
DOI: 10.3390/f11060639
|View full text |Cite
|
Sign up to set email alerts
|

Drought Resistance of Norway Spruce (Picea abies [L.] Karst) and European Beech (Fagus sylvatica [L.]) in Mixed vs. Monospecific Stands and on Dry vs. Wet Sites. From Evidence at the Tree Level to Relevance at the Stand Level

Abstract: Frequency of drought years is expected to increase through climate warming. Mixed stands have often shown to be more productive than monospecific stands in terms of yield and of resistance against windthrows and bark beetle attacks. Mixture of beech and spruce is of particular interest. However, little is known about its growth reaction to drought. Therefore, we investigated the drought reaction of beech and spruce in mixed vs. monospecific stands along an ecological gradient. In particular, we sought evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 83 publications
(143 reference statements)
1
2
0
Order By: Relevance
“…Our study identified significant differences among tree age-classes of managed Pinus nigra forest stands in terms of basal area increment (BAI), drought resistance, and drought resilience. These results support the argument that tree age can modify the drought impact in forest stands [14,68,69]. Our results showed that younger trees (<40 years of age) were more resistant and resilient to extreme droughts which occurred in 1981, 1991, 1999, and compared to older trees (40-120 years of age) (Figures 4 and 5).…”
Section: Discussionsupporting
confidence: 89%
“…Our study identified significant differences among tree age-classes of managed Pinus nigra forest stands in terms of basal area increment (BAI), drought resistance, and drought resilience. These results support the argument that tree age can modify the drought impact in forest stands [14,68,69]. Our results showed that younger trees (<40 years of age) were more resistant and resilient to extreme droughts which occurred in 1981, 1991, 1999, and compared to older trees (40-120 years of age) (Figures 4 and 5).…”
Section: Discussionsupporting
confidence: 89%
“…In 2003, partial or full branch diebacks, along with severe growth reductions were reported [87][88][89][90][91]. Growth recovery was often slow [3,24,92,93] and trees exhibited a significant growth decline after 2003 [3,94]. Upper branch dieback and formation of stag-headed patterns on the side branches led up to 70% loss of foliage on intermediate (height on average 10 m) and suppressed beech trees (below 10 m height) in Südbaden in Germany [92,95].…”
Section: Negative Impacts Of the 2003 Droughtmentioning
confidence: 99%
“…Since 2000, parts of Central Europe have experienced persistent hot and dry periods in summer and non-summer periods [24], leading to a greater risk of precipitation deficits combined with increased temperatures and evapotranspiration [25]. Precipitation deficits can lead to a tight hydrological balance and, potentially, plant water stress [26]; thus, concerns have been raised concerning the ecological stability and adaptation of drought-sensitive Norway spruce trees [22,27,28]. Boden et al [29] indicated a loss of growth resilience and stress response to decreasing water availability and a relatively limited short-term adaptive capacity to changing climate conditions in tree-ring width (TRW) series of Norway spruce trees located in southwestern Germany in sub-mountainous and mountainous belts.…”
Section: Introductionmentioning
confidence: 99%